Risk and Trust: The Lonely Journey of EFL Remote Teachers’ Integration of AI - Dinata, Ridho Praja; Basthomi, Yazid; Suryati, Nunung; Hasymi, Mutia; Rovikasari, Mala (Journal of Teaching and Learning, 2026)
Integrating Artificial Intelligence (AI) into 21st-century education has attracted significant attention, particularly in teaching English as a Foreign Language (EFL) in remote areas. This study explores the integration of risk and trust among EFL teachers in Indonesia as they incorporate AI tools into their teaching practices. Using a qualitative case study approach, the research focuses on two remote EFL teachers in Jambi, Indonesia, with at least four years of experience using AI. The data collection method included semi-structured interviews and teaching artifacts, focusing on AI integration, risk, and trust. This study employed thematic analysis to examine the data and identify the key themes in the perspectives of remote EFL teachers. The findings reveal that AI significantly enhances teaching preparation, streamlining tasks, tailoring learning materials, and analyzing student progress. Trust in AI, influenced by its usability, adaptability, and perceived benefits, plays a pivotal role in its successful adoption. However, notable risks accompany these merits, including over-reliance on AI, which may reduce critical thinking and creativity, as well as privacy and data security concerns. The results highlight the importance of striking a balance between AI integration and teacher expertise to mitigate risks and foster trust for achieving significant outcomes.